Quantitative analysis of 3D alignment quality: its impact on soft-validation, particle pruning and homogeneity analysis - Vargas, J. (Sci Rep, 2017)
Single Particle Analysis using cryo-electron microscopy is a structural biology technique aimed at capturing the three-dimensional (3D) conformation of biological macromolecules. Projection images used to construct the 3D density map are characterized by a very low signal-to-noise ratio to minimize radiation damage in the samples. As a consequence, the 3D image alignment process is a challenging and error prone task which usually determines the success or failure of obtaining a high quality map. In this work, we present an approach able to quantify the alignment precision and accuracy of the 3D alignment process, which is then being used to help the reconstruction process in a number of ways, such as: (1) Providing quality indicators of the macromolecular map for soft validation, (2) Assessing the degree of homogeneity of the sample and, (3), Selecting subsets of representative images. We present experimental results in which the quality of the finally obtained 3D maps is clearly improved.